New Psychoactive Substances: Major Groups, Laboratory Testing Challenges, Public Health Concerns, and Community-Based Solutions - Chinaza Godswill Awuchi; Maduabuchi Patrick Aja; Nancy Bonareri Mitaki; Sonia Morya; Ikechukwu O. Amagwula; Chinelo Kate Echeta; Victory S. Igwe (Journal of Chemistry)
Across communities worldwide, various new psychoactive substances (NPSs) continue to emerge, which worsens the challenges to global mental health, drug rules, and public health risks, as well as combats their usage. Specifically, the vast number of NPSs that are currently available, coupled with the rate at which new ones emerge worldwide, increasingly challenges both forensic and clinical testing strategies. The well-established NPS detection techniques include immunoassays, colorimetric tests, mass spectrometric techniques, chromatographic techniques, and hyphenated types. Nonetheless, mitigating drug abuse and NPS usage is achievable through extensive community-based initiatives, with increased focus on harm reduction. Clinically validated and reliable testing of NPS from human samples, along with community-driven solution, such as harm reduction, will be of great importance, especially in combating their prevalence and the use of other illicit synthetic substances. There is a need for continued literature synthesis to reiterate the importance of NPS, given the continuous emergence of illicit substances in the recent years. All these are discussed in this overview, as we performed another look into NPS, from differentiating the major groups and identifying with laboratory testing challenges to community-based initiatives.